2017
DOI: 10.1007/s11116-017-9811-1
|View full text |Cite
|
Sign up to set email alerts
|

Tracking a system of shared autonomous vehicles across the Austin, Texas network using agent-based simulation

Abstract: This study provides a large-scale micro-simulation of transportation patterns in a metropolitan area when relying on a system of shared autonomous vehicles (SAVs). The six-county region of Austin, Texas is used for its land development patterns, demographics, networks, and trip tables. The agent-based MATSim toolkit allows modelers to track individual travelers and individual vehicles, with great temporal and spatial detail. MATSim's algorithms help improve individual travel plans (by changing tour and trip st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
83
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(95 citation statements)
references
References 13 publications
1
83
0
1
Order By: Relevance
“…Existing research on AV mainly focuses on macro-level analysis, including policy issues [7,16], legislative supervision [17], SAV dispatch optimization [5,18,19] and the impact on traditional transportation system [5,20,21]. In the study of user behavior at the micro-level, individuals' travel mode choice behavior in AV and SAV mobility behavior has already become a hot research topic and recently get more attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research on AV mainly focuses on macro-level analysis, including policy issues [7,16], legislative supervision [17], SAV dispatch optimization [5,18,19] and the impact on traditional transportation system [5,20,21]. In the study of user behavior at the micro-level, individuals' travel mode choice behavior in AV and SAV mobility behavior has already become a hot research topic and recently get more attention.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of user behavior at the micro-level, individuals' travel mode choice behavior in AV and SAV mobility behavior has already become a hot research topic and recently get more attention. However, the travel mode model used in the study of AV choice behavior mainly regards socioeconomic attribute and travel mode attribute as the explanatory variables of the model [19,[22][23][24][25][26], while ignoring the intrinsic influence brought by the individual's preference heterogeneity. In recent years, only a few studies have focused on psychological factors such as safety, technology interest, or environmental concern [13,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…One step into this direction has already been taken by Liu et al [29], who addressed the problem from the perspective of mode shifts and empty rides.…”
mentioning
confidence: 99%
“…Therefore, the model can be used to simulate traffic flow and residents' behaviors in urban transport, including the residents' choice of travel modes [31] and carpooling models [32]. Other research applications are found in the optimization of bus routes [33,34], the simulation of the functioning of the urban composite transportation system [35], the evaluation of the impact of the intercity high-speed railway on the ecological environment [36], etc. From the perspective of development trends in research, studies are moving from the simulation of individual decision-making to that of the composite flow of urban traffic, with increasing complexity of simulation.…”
mentioning
confidence: 99%